Constructing timber architecture : merging the skills of architect, carpenter and masonry workers - Said, Ismail; Desa, Abdul Malek; Syed Ariffin, Syed Ahmad lskandar (Faculty of Built Environment, UTM, 2008)
Carpentry skill in constructing timber architecture is fast vanishing in Malaysian building industry. As such mass housing schemes are dominated by masonry architecture, leaving the skills of working with timber only to construct the roof frames and doorways. High cost of timber relative to masonry is one of the influencing factors for the industry to put aside the value of timber architecture. Notwithstanding, the carpentry skills in making furniture, doors and windows are available in small to medium scales. This paper presents a real project of constructing small-scale timber architecture by merging the skills of furniture carpenter with the skills of masonry workers. A freshly developed means of communication and working environment comes almost naturally to allow the three parties to work in coherent to the objective. Timber building components which require top level precision are prepared by the carpenter. On-site building erection and assembly process are left to the masonry workers who are obviously the most capable. Completed timber components are carted to the site, and assembled by the masonry workers, and when necessary assisted by the carpentry workers. The masonry group takes the heavy-duty tasks such as lifting and positioning the posts on the stumps and fixing the beams into the mortises prepared by the carpenters. And, the carpentry group does the finishing tasks including painting. The architect coordinates the two teams with reference to the drawing and some work specifications. It is found that through accurate drawings and skills of furniture carpenter and masonry workers the construction of a high quality standard timber building is feasible.